Sex-Related Differences in the Developmental Morphology of the Atlas: A Computed Tomography Study. Issue 10 (15th May 2018) - Asukai, Mitsuru; Fujita, Tomotada; Suzuki, Daisuke; Nishida, Tatsuya; Ohishi, Tsuyoshi; Matsuyama, Yukihiro
Abstract : Study Design: A retrospective study. Objective: To elucidate sex-related differences in the age at synchondroses closure, the normative size of the atlas, and the ossification patterns of the atlas in Japanese children. Summary of Background Data: The atlas develops from three ossification centers during childhood. The anterior and posterior synchondroses, which are separate ossification centers, mimic fracture lines on computed tomography (CT). Sex-related differences of age dependent morphological changes of the atlas in a large sample size have not been reported. Methods: This study analyzed data of 688 subjects (449 boys) between 0 and 18 years old who underwent CT examination of the head and/or neck between January 2010 and July 2016. The age at synchondroses closure, anteroposterior outer, inner, and spinal canal widths of the atlas, and variations of the ossification centers were examined. Results: Anterior synchondroses closed by 10 years in boys and by 7 years in girls. Significant earlier closure of anterior synchondroses was observed in girls than in boys ( P < 0.05 at 4 and 5 years old). Posterior synchondrosis closed by 6 years in boys and by 5 years in girls. The outer, inner, and spinal canal widths increased up to 10 to 15 years in both sexes, although all three parameters in girls peaked 3 years earlier than those in boys. All parameters in boys were significantly larger than those in girls, except in the 10- to 12-year-old age category. Two or more ossification centers in the anterior arch were observed in 18.3% subjects, and 6% had midline ossification centers in the posterior arch of the atlas. Conclusion: Distinct sex-related differences in the age at anterior synchondroses closure and the size of the atlas were observed in Japanese children. Knowledge of morphological features of the atlas could help distinguish fractures from synchondroses. Level of Evidence: 3